Matter of Superiority Complex as Depicted on Leo Tolstoy’s The Three Hermits - Axlinabila Annisa Annasai; Kusuma Wijaya; Rommel Utungga Pasopati (Proceeding International Conference on Religion, Science and Education, 2023)
Literature is nothing but conception of attitude of human beings. Superior complex is a pompous attitude that relates to concept of holier-than-thou as stated by Alfred Adler. People, as individual or social, in this attitude think that their level is higher than others. The Three Hermits is Leo Tolstoy’s short story published in 1886. This classic story tells a bishop who sees three holy men in a remote island then teaches them how to pray. He is so proud that he could spread the teaching of Christ, but then he is shocked by latter miracle done by those three men. Then, how is superiority complex depicted on Leo Tolstoy’s The Three Hermits? Through qualitative method on cultural studies, this writing explains superiority complex as monolithic conception that solely thinks a side is totally better than the other. The bishop’s attitude thinks that he is a legitimate bearer of truth from God. He is curious at first but then thinks that he is ordained to speak the only truth to others. He ignores plurality of otherness by only believing his deed is the truest one as also supported by Adler’s theory. In conclusion, the story shows how being superior ignores matter of otherness. The bishop omits possibilities of other truth while otherness is more complex than he thinks.